Męka Chrystusa w rękopiśmiennej poezji karmelitańskiej - Kaczor, Katarzyna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2002)
Before approaching the problem of „The Torment of Christ in Polish Carmelitan Poetry Manuscripts” , it was necessary, specifically for the purpose of this work, to consider the problem of the beginning passion of Christ in Polish poetry in the 13th century. The sources creative invention, as in art and literature in the Middle Ages is evangelical dramatic torment of Christ. This subject presents mediaeval liturgical dramas, passion’s mysteries, meditations, saint biographies, legends, etc. The inspiration for literature is dolorysm and a picture of pieta. In mediaeval Polish literature are very alive characteristics of passion’s motifs: meditation, compassion and imitation torment of Christ. Such a popular subject in the Middle Ages, the torment of Christ was also present in a rich array of literature in the 17th century. This article deals how the problem of the torment of Christ was visible in Polish carmelitan poetry manuscripts from 17th and 18th centuries. These carmelitan manuscript texts, which I research in this work, are contained in the Library of Jagiellonia and they have signatures: 3640 and 3642. The article also shows the influence of mysticism of St. Teresa of Avila and of St. John of the Cross in these manuscripts, but shows as well the original conception of Cracow’s anonymous poets from the 17th century. This work particularly presents the personal experiences of Cracow’s carmelitans (dialogue with God, the love to Him, a need of suffering how Christ and the need of death). This article shows not only carmelitan literary ingeniousness, but also a personal metaphysical and mystical way to the soul of God.